Students' Reported Political Engagement and Knowledge in a Politically Charge Environment - Daley, Caitlin; Nelson, Renee; Ellefson, Sydney; Drewiske, Kim; Carlson, Katie (My University, 2015)
Research has shown that student involvement on college campuses is associated with their overall college satisfaction (Webber, Krylow, Zhang, 2013) and that college students have low political knowledge and involvement (Bernstein, 2005; Beaumont, Colby, Ehrlich, & Torney-Purta, 2006). At the University of Wisconsin - Eau Claire, the campus climate is currently politically charged due to proposed economic challenges, specifically the proposed state mandated budget cuts to the University of Wisconsin System. Based on Impression Management Theory, in a social situation where high political knowledge may be expected, it is possible that students either over report their knowledge or decide not to become involved in political activities. This study surveyed students at the University of Wisconsin - Eau Claire to test for relationships between reported political involvement and knowledge and impression management efforts. Findings are useful for understanding how students self-report their knowledge and involvement in a politically charged climate.
Color poster with text, graphs, and photographs.
Keywords: Posters; Political climate; University budgets; Budget cuts